DEVELOPMENT OF TECHNOLOGY OF COTTAGE CHEESE PRODUCT USING WILD PLANT RAW MATERIALS OF SEA-BUCKTHORN AND NETTLE - Sazhenova Y.M.; Lupinskaya S.M. (Техника и технология пищевых производств)
The use of local wild plant raw material resources in the food industry contributes to the solution of the problem of import substitution thus ensuring food security of the population of Russia. The wild plant raw materials of nettle and sea-buckthorn belong to perspective types of plant raw materials for production of enriched foods and highly effective food additives. Considering valuable properties and abundance of sea-buckthorn and nettle in the Siberian region the possibility of creation of milk based food products enriched with them has been studied. The modeling of prophylactic food is based on fundamental tenets of food science . The technology has been developed, and the technological scheme of production of a cottage cheese product enriched with biologically active substances of nettle and sea-buckthorn is given. Organoleptic and physical-and-chemical indices of a cottage cheese product have been investigated. The nutritive, energy and biological value of a product has been determined. The developed product belongs to protein dairy products with balanced amino-acid content. It is a low-in-fat product of a low energy value. The use of wild plant raw material of nettle in a compounding of a cottage cheese product makes it possible to raise the score of the first limiting metionin+tsistein acid by 6.7%. In comparison with traditional cottage cheese products the developed product is enriched with ?- carotine and vitamin C performing antioxidant protection of the body and improving protein and calcium assimilation. The use of local resources of wild plant raw materials in the dairy industry will make it possible to widen the assortment of foods of improved nutritional value and enriched content which are in consumers’ demand and hence to increase competitiveness and efficiency of enterprises.